Evaluation of the effect of state subsidies on business - Ginevičius, Romualdas; Bruzgė, Šarūnas (Business, Management and Economics Engineering, 2013)
The effect of market regulation tools on business is a complex phenomenon, and the after-effects of such regulation could be both favourable and adverse. The enhancement of the positive effect is a scientific task, which requires a systematic approach. In order to find a solution to this problem, it is necessary: a) to identify the relevant factors; b) to make a coherent evaluation of these factors and their influence on the phenomenon under investigation; c) to establish the optimal form and extent of the SRB (State Regulation of Business) tool required for the achievement of the desired results. The study analyses aims of economic regulation and business management from the point of view of a state. It also examines the practice in economic research and evaluation of EU Structural Funds in Lithuania and abroad. The research is focused on problems caused by state subsidies for business enterprises as one of the forms of SRB. The research also focuses on possibilities to enhance the effectiveness of business regulation. The main objects of this study are: state subsidies for business enterprises as a form of state intervention in the market, and the possible correlation between the specifications of subsidies and their effect on business. The evaluation presented in this study proved that EU subsidies had a direct positive influence on the effect of subsidies. The research into the influence of various subsidy criteria on the effect of subsidies revealed that a greater effect results from the rate rather than the size of funding.